Sexual Dysfunction after Radical Prostatectomy - McCullough, Andrew R (MedReviews, LLC, 2005)
Sexual dysfunction associated with radical retropubic prostatectomy (RRP) may start before the surgery. Men undergoing RRP frequently have some degree of sexual dysfunction. In addition to the psychological stress of the diagnosis, the biopsy may itself have a detrimental effect. After surgery, all men will experience loss of ejaculate, because the organ responsible for ejaculate has been removed. Orgasm quality is adversely affected in many men. Erectile dysfunction is immediate and recovery from it is slow. Initially, phosphodiesterase (PDE)-5 inhibitors do not work, and they take up to 18 months for their effect to be maximized. Younger men who have had bilateral nerve-sparing procedures respond the best. Combination treatment with prostaglandin E1 or high-dose PDE-5 inhibitors may provide salvage therapy when initial PDE-5 inhibitor therapy has failed.